Why do people with dementia pretend to know the correct answer? A qualitative study on the behaviour of toritsukuroi to keep up appearances. Issue 6 (4th April 2017) - Matsushita, Masateru; Yatabe, Yusuke; Koyama, Asuka; Ueno, Yukiko; Ijichi, Daisuke; Ikezaki, Hiroto; Hashimoto, Mamoru; Furukawa, Noboru; Ikeda, Manabu
Abstract : Background: Toritsukuroi is a particular type of behaviour intended to save face or preserve appearances. Clinicians often observe toritsukuroi in people with dementia, but current knowledge about this behaviour is based on clinicians' empirical knowledge rather than on observational studies. This study was designed to clarify which behaviours are related to toritsukuroi based on neuropsychological examinations. Methods: The subjects were 91 outpatients with dementia. Verbal responses, with the exceptions of 'I don't know' and erroneous answers, were recorded by certificated clinical psychologists and analyzed by qualitative study procedures. A qualitative study was separately conducted by two researchers to identify themes and types of reactions. The themes found through content analysis were organized and labelled by a senior psychiatrist. Results: Among the patients, 41.8% verbally responded in way to 'keep up appearances'. Six distinct thematic categories were identified through conventional content analysis: (i) refuting sudden questions; (ii) disclosing trait; (iii) disclosing experience; (iv) demonstrating slight hesitation; (v) appealing to indifference; and (vi) other. Conclusions: All the responses that we defined as being toritsukuroi reflect a denial of acquired cognitive impairment. Further study is needed to clarify the association between toritsukuroi and either cognitive function or disease specificity.